Electrochemical treatment of hemodialysis wastewater including pharmaceutical products. (1st January 2023) - González-Nava, V.J.; Bacame-Valenzuela, F.J.; Reyes-Vidal, Y.; Manríquez, J.; Sepúlveda-Guzmán, S.; Bustos, E.
Highlights: Coupled electrocoagulation and electro-oxidation were successfully used. Stainless steel and aluminum were studied as anode materials during electrocoagulation. The supernatant from electrocoagulation was treated with electro-oxidation using an Iro2 -Ta2 O5 |Ti anode. The coupled treatment system completely eliminated amoxicillin. The coupled treatment system significantly reduced entrained salts. Abstract: Hemodialysis is an extracorporeal kidney replacement procedure to remove impurities or waste products from the blood that is used in the treatment of kidney failure. During this process, large amounts of water are used, which, lacking control, end up in sewage systems, potentially flushing high levels of organic and inorganic contaminants into the receiver's aqua biota. This research considered the treatment of synthetic hemodialysis water under acid and basic conditions. To better simulate the presence of organic compounds, 10 mg L −1 of amoxicillin, an antibiotic commonly present in wastewater from clinics and hospitals, was added. Laboratory and pilot tests were performed using coupled electrocoagulation and electro-oxidation. During electrocoagulation, the use of stainless steel and aluminum, as sacrificial anodes, were compared in acidic and basic pH. The stainless steel rod anode and a titanium mesh cathode were used during electrocoagulation in acidic conditions at a field strength of 3.0 V which was applied for 60 min. After electrocoagulation, the solution obtained was filtered to separate precipitates. The supernatant was then treated with electro-oxidation using an IrO2 -Ta2 O5 |Ti anode and the titanium mesh cathode while applying 10 mA for 120 min. Wear of the stainless steel anode was identified by scanning electron microscopy and microanalysis. Removal of organic compounds including amoxicillin was significant. These results were confirmed by decreased contaminant concentration found by diode coupled chromatography detection. In the final analysis this coupled treatment system completely eliminated amoxicillin and significantly reduced entrained salts. Graphical abstract: Image, graphical abstract